Effects of Problem-Based Learning on Biology Learning Outcomes of Phase E Students: A Meta-Analysis - Bekti Isnaeni (Scientiae Educatia: Jurnal Pendidikan Sains, 2025)
This study aims to analyze and empirically substantiate the effects of the Problem-Based Learning (PBL) model on the biology learning outcomes of Phase E students. A meta-analysis research design was employed as the primary methodological framework. Data were collected through systematic documentation by retrieving journal articles using the following keywords: "PBL model," "biology learning outcomes," "class X," "PTK," and "MCML > 75" via Google Scholar. A total of 25 journal articles published within the period 2019–2024 satisfied the inclusion criteria and were retained for analysis. Data analysis was conducted using JASP software (version 0.8.4.0) to perform heterogeneity tests, hypothesis tests, and publication bias assessments. The outputs generated by JASP were subsequently interpreted based on relevant scholarly literature pertaining to meta-analytic methodology. Conclusions were drawn on the basis of how each research question was addressed through the corresponding statistical tests. The findings demonstrate that the PBL model exerted a significant positive effect on the improvement of biology learning outcomes among Phase E students, yielding an effect size (ES) value of 0.88, which falls within the high category. Furthermore, the analysis confirms the absence of publication bias, as evidenced by the funnel plot symmetry, the non-significant p-value obtained from the Egger test, and a fail-safe N value exceeding the threshold of 5k + 10, thereby affirming the scientific robustness and reliability of the reported findings. On the basis of these results, it is recommended that future researchers conduct more in-depth investigations into the PBL model across diverse biological content areas. It is further recommended that teachers and educational policymakers ensure that the problems presented during the problem-orientation phase are genuinely contextual and current, thereby fostering greater student participation in collaborative group discussions and ultimately enhancing overall biology learning outcomes.